Stimulation of the Semicircular Canals or the Utricles by Clinical Tests Can Modify the Intensity of Phantom Limb Pain - Aranda-Moreno, Catalina; Jáuregui-Renaud, Kathrine; Reyes-Espinosa, Jaime; Andrade-Galicia, Angelina; Bastida-Segura, Ana E.; González Carrazco, Lourdes G. (Frontiers in Neurology, 2019)
Background: After amputation, phantom limb pain may be produced by the multisensory processes underling the experience of an intact body. Clinical evidence has shown that cold caloric vestibular stimulation may modify the perception of phantom limb pain. However, it is yet unknown if this effect can be observed after the mild vestibular stimulation given by the clinical caloric test, or after utricle stimulation by centrifugation. Additionally, there are no studies on the association between the report of altered perceptions or experience of the self or the environment (depersonalization/ derealization symptoms) and phantom limb pain. Objective: To assess the influence of unilateral stimulation of the horizontal semicircular canals by clinical caloric test, and the utricles by unilateral centrifugation on the intensity of phantom limb pain, and to explore the association between phantom limb pain and symptoms of depersonalization/ derealization. Methods: 34 patients (56 ±7 years old, 23 men) accepted to participate after 3 to 23 months of unilateral supracondylar amputation, secondary to type 2 diabetes mellitus. After assessment of vestibular function and symptoms of common mental disorders, using a cross-over design, in 2 separate sessions with one week in between, vestibular stimulation was delivered by right/ left caloric test (30°C or 44°C) or right/ left centrifugation (3.85 cm, 300°/s peak). Before and after each vestibular stimulus, the intensity of phantom limb pain and depersonalization/derealization symptoms were assessed, with a daily follow-up of pain intensity during one week. Results: Either caloric stimulation or unilateral centrifugation decreased phantom limb pain (p<0.05), along with decrease of symptoms of depersonalization/derealization (p<0.05). One third of the patients reporting pain decrease immediately after stimulation also reported no pain at least for 1 day. Limitations: No sham condition was included. Conclusions: Vestibular stimulation by the clinical caloric tests or by unilateral centrifugation may decrease the intensity of phantom limb pain, with decrease of perceptions of unreality. These effects might be related to an update of the immediate experience of the body, given by the sensory mismatch induced by asymmetrical vestibular stimulation.